Integrated Rudder/Fin Concise Control Based on Frequency Domain Analysis - W. Guan; Z. J. Su; G. Q. Zhang (Indonesian Journal of Electrical Engineering and Computer Science, 2013)
This paper describes a concise robust controller design of integrated rudder and fin control system in use of the closed loop gain shaping algorithm (CGSA) strategy. Compared with the arbitrary selection of weighting function in integrated rudder and fin H∞ mixed sensitivity control design procedures, the CGSA methods provided a relatively more straightforward and concise design method. Simulations were described that the overall performance of each CGSA rudder and fin control loop and the interaction between them. Hence, it can be concluded that the integrated rudder and fin CGSA control scheme is very suitable to present and indeed feasible for future practical application. DOI: http://dx.doi.org/10.11591/telkomnika.v11i7.2834